Pengelolaan Dana Desa Dalam Pelaksanaan Pembangunan Di Desa Sangsit - Mahena, Komang Mahena; Nyoman Ari Surya Darmawan (Vokasi : Jurnal Riset Akuntansi, 2025)
Based on the results of research conducted on the analysis of Village Fund management in relation to development implementation in Sangsit Village, it can be concluded that: Planning is the careful, structured, and thoughtful preparation of concepts for future activities. Planning in Village Fund management is structured periodically and determined in accordance with Village Regulations (PerDes). In an interview with the Sangsit Village Secretary, the first step in planning is the formation of an implementation team, which is held during the Village Development Planning Meeting. Implementation is the stage of realizing the previously developed plan, where all village income and expenditure are managed through the village cash account. Based on observations in Sangsit Village, several development activities were realized in 2024 according to the established plan. Administration is a crucial activity in village financial management, encompassing recording, inventory, and reporting to ensure orderly and effective management. This task is the responsibility of the village treasurer, who is required to record all income and expenditure and prepare a monthly accountability report (LPJ). Based on an interview with Mrs. Made Suryani, as the head of financial affairs of Sangsit Village, she stated that she routinely records the income and expenditure of village funds for development, then compiles them in a monthly report which is submitted in the LPJ forum. Reporting is the delivery of information related to certain activities or conditions to the authorities, while accountability is the obligation to explain and accept the consequences of actions taken. In the reporting stage, the village treasurer still plays an important role because he is tasked with recording the flow of funds in and out. Meanwhile, in the accountability stage, the main role is held by the Village Head who submits a report on the realization of the Village Budget (APB) to the Regent in two stages, namely the first semester and year-end reports. To the people of Sangsit Village, accountability information is conveyed through banners installed at the construction site or in front of the Village Office.